2021
DOI: 10.1093/braincomms/fcab071
|View full text |Cite
|
Sign up to set email alerts
|

High neutrophil/lymphocyte ratio at cancer diagnosis predicts incidence of stroke in cancer patients

Abstract: Although cancer increases the incidence and severity of ischemic stroke, there is no reliable method for predicting ischemic stroke in cancer patients. To evaluate the prognostic capacity of the neutrophil-to-lymphocyte ratio at cancer diagnosis for predicting the incidence of ischemic stroke, we used a hospital-based cancer registry that contained clinical data from all patients treated for cancer at Osaka University Hospital between 2007 and 2015. The neutrophil-to-lymphocyte ratio was calculated after divid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…NLR is also an important predictor of AF prognosis ( 7 ). It has been reported that NLR can be used to assess stroke risk and prognosis in AF patients ( 8 10 ), but there are also studies that suggest that NLR is not an independent biomarker for predicting stroke ( 11 ). Therefore, the ability of NLR to independently assess or predict stroke risk in AF patients remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…NLR is also an important predictor of AF prognosis ( 7 ). It has been reported that NLR can be used to assess stroke risk and prognosis in AF patients ( 8 10 ), but there are also studies that suggest that NLR is not an independent biomarker for predicting stroke ( 11 ). Therefore, the ability of NLR to independently assess or predict stroke risk in AF patients remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…Lower body mass index and marginally less obese patients can be found with a preoperative PLR > 160[ 53 ], NLR of patients with T2DM or hypertension do not differ from those without the two conditions[ 54 ], LMR combined with carbohydrate antigen 19-9 has good predictive value on postoperative recurrence in CRC + T2DM patients[ 55 ], and PLR is significantly higher in CRC patients with metabolic syndrome[ 56 ]. Furthermore, colorectal adenoma, which has a high risk to develop into CRC[ 57 ], has an increased prevalence in metabolic syndrome patients with higher NLR values[ 23 ], and higher NLR at the diagnosis of CRC may be a sign of stroke within 2 years after cancer diagnosis[ 58 ]. We found that preoperative RPR was marginally and significantly higher in those CRC patients with T2DM and previous major CV event in their medical history, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have made a variety of efforts, and these studies have evaluated several factors, such as increased levels of DD, C-reactive protein and neutrophil/lymphocyte ratio in the blood and the presence of multiple ischemic lesions in neuroimaging, which have been used as biomarkers of cancer-related ischemic stroke. [27][28][29][30] However, due to the lack of specific substances or measures, the precise measures to identify cancer-related cerebral infarction are still unclear. In this study, considering that the three independent risk factors for ECIS may play their own roles or may play a role together as a factor in the development of ECIS, we established an ROC curve to identify the factors that play the greatest role in the development of ECIS.…”
Section: Discussionmentioning
confidence: 99%